Characterizing pain flares in adolescent inflammatory and non‐inflammatory musculoskeletal disorders: A qualitative study using an interpretative phenomenological approach. (19th July 2020) - Khanom, Sonia; McDonagh, Janet E.; Briggs, Michelle; McBeth, John
Abstract: Background: Adolescents with musculoskeletal disorders experience acute exacerbations in pain, colloquially called "pain flares" in adult literature. This study aimed to explore adolescents' lived experience of pain flares, including what pain flares are, why they occur, how they are managed and what lasting effects they have on adolescents. Methods: A sample of 10 adolescents diagnosed with juvenile idiopathic arthritis or chronic idiopathic pain syndrome were recruited from a tertiary hospital in the UK. Data were collected using semi‐structured interviews and visual aids, and analysed using interpretative phenomenological analysis. Results: Four broad themes were identified which describe as a journey of change from participants: (a) daily life with pain, where adolescents report a level of pain that is "normal" for them which they can tolerate and continue their daily routines around; (b) pre‐flare period, where adolescents begin to notice pain increasing beyond normal levels and employ preventative strategies to reduce the risk of symptoms developing into a flare; (c) flare period, where adolescents describe the symptoms, frequency, duration, impact and their attempts to manage flares; to their (d) post‐flare period, where symptoms begin to return to baseline levels and adolescents take actions to regain the level of normality experienced in daily life. Conclusion: This study has identified a number of components of the pain flare experience. Findings show that pain flares are more than an increase in pain intensity; they are multi‐layered and require other features to change. These findings help to differentiate pain flares from typical fluctuations in pain.